Composition, Sequencing and Ion Mobility Mass Spectrometry of Heparan Sulfate-like Octasaccharide Isomers Differing in Glucuronic and Iduronic Acid Content. Issue 3 (June 2015) - Miller, Rebecca L.; Wei, Wei; Schwörer, Ralf; Zubkova, Olga V.; Tyler, Peter C.; Turnbull, Jeremy E.; Leary, Julie A.
Here we report ion mobility mass spectrometry (IMMS) separation and tandem mass spectrometry (MS 2 ) sequencing methods used to analyze and differentiate six synthetically produced heparin/heparan sulfate (HS)-like octasaccharide (dp8) isomeric structures. These structures are isomeric with regard to either glucuronic acid (GlcA) or iduronic acid (IdoA) residues at various positions. IMMS analysis showed that a fully GlcA structure exhibited a more compact conformation, whereas the fully IdoA structure was more extended. Interestingly, the change from IdoA to GlcA in specific locations resulted in strong conformational distortions. MS 2 of the six isomers showed very different spectra with unique sets of diagnostic product ions. Analysis of MS 2 product ion spectra suggests that the GlcA group correlated with the formation of a glycosidic product ion under lower energy conditions. This resulted in an earlier product ion formation and more intense product ions. Importantly, this knowledge enabled a complete sequencing of the positions of GlcA and IdoA in each of the four positions located in each unique dp8 structure.